İkinci harmonik savaktan pompalamalı dağılmış parametreli karıştırıcı tasarımı - Ordu, Mustafa Tuna (Fen Bilimleri Enstitüsü, 1995)
Bu tez çalışmasında, 2-12 GHz frekans bandındaki RF işaretini 70 MHz lik ara frekans işaretine dönüştüren dağılmış parametreli karıştırıcı tasarımı yapılmıştır. Tasarımın gerçekleştirilmesinde Microwave Harmonica programından yararlanılmıştır. Karıştırıcıda doğrusal olmayan eleman olarak MESFET'ler kullanılmıştır. MESFET'ler NE 71000 serisi seçilmiştir. Üç MESFET kaskat bağlanarak istenen kazanç ve band genişliği sağlanmıştır. Devre elemanlarının MH da optimize edilmesiyle en iyi değerleri bulunmuş ve daha sonra bu elemanlar mikrostrip hat olarak gerçekleştirilmiştir. Devre dielektrik sabiti (eR) 2,22 ve kalınlığı (h) 0,4 mm olan Duroide 5880 taban üzerine tasarlanmıştır. Boğucu bobin ve köprüleme kapasiteleri hariç diğer tüm elemanlar mikrostrip hat olarak kullanılmıştır.

Subharmonically drain pumped distributed mixer design has been realized at this master thesis, through help of the program, Microwave Harmonica. Mixers are generally employed at conversion of data signal's frequency to that of appropriate frequencies for transmittance. Theoritically, the mixing process is a multiplication by using properties of nonlinear elements. The block diagram of ideal mixer is given figure 1. Mt)coswA -Bf- Multiplier IF Down converter : 1/2A(t)Cos(ws-oop}t High-or low pass filter LO Cos wpt Up -Converter: 1/2 A(t)Cos(u>s+Wp) t Figure 1. Ideal mixer When A(t)Coso)st is employed at input of mixer togetherwith CosoL0t sign as local oscillator, then, mixer output shall generate following components: A (t) Cos ca t Cos (*L0t=A(t) -Cos(us - coİO)f + -(«, + co^f There are a number of basic parameters used in definition of mixers, which may be listed as; noise figure of mixer, intermodulation products and conversion gain (or loss). Noise figure by mixer may be defined as, relation between the ratio of signal to noise at the output and, ratio of signal to noise at the input. Nonlinear elements cause forming of components at no^Tmw^ frequencies during process of mixing, which further are called the intermodulation products. Conversion gain (or loss) may be defined, as the ratio of IF output power to RF input power. -v-Procedure applied at those subharmonically pumped mixers is harmonic pumping of IF (difference of the higher harmonic of the signal and LO frequencies). General properties of such mixers may be listed as follows: a) Conversion efficiency of such mixers are worse than those of first type mixers functioning at same frequency and same pumping power (LO). b) In low IF first harmomic pumped mixers, despite it is hard to achieve insulation between signal (RF) and local oscillator (LO), the same is attained rather easily at these mixers. c) Pumping frequency (LO) is equal to one-half of the LO frequency of first harmonic pumped mixer. d) If the first harmonic mixing products are suppressed, the IF noise of the LO may be diminished. This property is demonstrated at Figure 2. fr FH-=FRp-2FLO F F F NL LO NH 2F LO FRP ?*F Figure 2. Noise sidebands of local oscillator When first harmonic mixing products are eliminated, the IF noise due to mixing of FNL and FLO or, FNH and FL0, shall be supressed. Noise due to mixing of FNL to 2FLO, and FNH to 2FL0 side bands shall be retained out of the frequency band. Most circuit parameters of FET are connected to DC polarization. When a low level signal and LO signal are applied to an FET, the modulated circuit -vi-elements shall cause formation of signalling power converted to other frequencies. As lay be seen from Figure 3, some elements of the large signal model change, according to frequency to the signal applied. Lg Rg Cdg(Vg.Vd) I cgs (vg.vd)=j^vg(t) ffi% JZg(nu)L0) Ri|Id(ygyd) 0VLOCO5(U)Lot) Rdr Ld -AA/- r,nr>-o = C D 'ds Vgd"^ Z^nu^) ^V, db Figure 3. Large signal equivalent circuit of an FET mixer From this model, following termology may be derived for id(t) current: i£)=Hl+W2)tznh(aV2XVrVT)2 (1) where a, 13, *, VT used here are those parameters found by method employed in Appendix B. If an optimization is realized for objective function F, then, F = 1 N N(maxIJ £i E ck-y (2) shall be found. Where, N : measured number of points of DC characteristics. IjjjI : measured value of drain current at point i. Icj : calculated drain current value of (1) expression. Distributed mixer may be analyzed through a mutual examination of the distributed amplifier and the FET mixer theory. Drain and gates of MESFET's of -vii-such mixers may be considered as tranmission lines. Drain and gate transmission lines, when used as downconverters, must have equal phase shifts as a function of the frequency. Using equal phase shifts between LO and RF signals at each FET yields a constant phase offset at the IF frequency, which allows the IF power to be summed in phase. Consider a unilateral simplified model of a distributed mixer incorporating a gate line and a drain line, as shown in fig. 4. Drain line 4Xi(t)  n is the "umber of FET's. (1 1) -ix-The output IF power is given by: 1/ I2 ** = ^r Re\z> M (12) In this situation, conversion gain or loss may be determined as dB in the form PIF "SF In this master thesis, MESFET's of NE 71000 series was employed. According to modelling of these MESFET a program in Microwave Harmonica was issued, and through optimization of this program, final values of the circuit's elements were determined. Frequency band of the circuit was chosen as 2-12 GHz. IF frequency was taken as 70 MHz. The circuit was realized dielectric constant (eR) 2.22 and height (h) 0,4 mm Duroide 5880 base. All elements other than those of RF choke bobins and padding capacitances, were designed of the microstrip line.
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 1995
Keywords: Bilgisayar destekli tasarım; Karıştırıcılar; Computer aided design; Mixers